Peran Jurnalistik Islam dalam Menyampaikan Pesan Perdamaian (Studi pada Media Online Islam di Indonesia): (Studi pada Media Online Islam di Indonesia) - Mustafa; Kahinah, Dwi Iin; Masseni; Rezeki, Syailendra Reza Irwansyah; Purnamayanti, Irma (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam (IAI) Al-Aziziyah Samalanga, 2024)
Islamic online media in Indonesia plays a vital role in promoting messages of peace within a diverse society. This study aims to explore the journalistic strategies employed by Islamic online media to foster peace. Using a literature review approach, the study conducts an in-depth analysis of relevant content from Islamic online media. The findings reveal that Islamic online media adopt inclusive approaches, constructive diction, and multimedia formats such as videos, infographics, and podcasts to amplify the reach of peace messages. Additionally, these media outlets facilitate public dialogue through online discussion forums, which help mitigate opinion polarization. This research contributes to the academic literature by offering new insights into the role of Islamic media as peace agents and their relevance in Indonesia's digital society.